Investigating the relationship between inflammatory cytokines and adolescent depression: a comparative analysis - Liu, Mengqi; Tang, Jie; Xu, Gaoyang; Chen, Xu; Fang, Kun; He, Fan; Zheng, Yi (Frontiers in Psychiatry, 2025)
BackgroundMajor depressive disorder (MDD) in adolescents poses a significant threat to physical health. Previous studies have indicated that adolescents with MDD exhibit immune activation.ObjectiveThis study aimed to compare cytokine levels in adolescents with MDD to healthy controls and assess their diagnostic value.MethodsThis cross-sectional study included 58 adolescent patients with depression from Beijing Anding Hospital (outpatients and inpatients) and 40 healthy adolescents recruited from the community. Multiplex cytokine analysis (Luminex xMAP) was used to measure serum levels of several cytokines. Data analysis was performed using SPSS (version 26.0) to compare cytokine levels between adolescents with MDD and healthy controls and assess gender differences. Correlations between cytokine levels and demographic data, clinical features and depressive symptoms were also analyzed. The receiver operating characteristic (ROC) curves were used to evaluate the diagnostic value of cytokines.ResultsSerum IL-4, IFN-γ, and TNF-α levels were significantly elevated in MDD group compared with healthy controls (p < 0.05). In MDD group, the age of first onset of depression in females was significantly younger than that in males (p < 0.05), and female serum TNF-α levels were significantly higher than those in males (p < 0.05). BMI and serum IL-4 levels were significantly positively correlated in adolescents with MDD. The area under the ROC curve for serum IL-4 and TNF-α in diagnosing adolescent depression was 0.695 (95% confidence interval [CI]: 0.580 - 0.809; p < 0.05), with a sensitivity of 0.793 and specificity of 0.675.ConclusionCompared with healthy controls, adolescents with depression demonstrated significantly elevated serum cytokine levels, indicating immune activation which were higher in female. Cytokines may have promising diagnostic value in adolescent depression, but further validation with additional indicators is needed.